Public Art And The Impact It Has On The Society - Hilary Adina Theresa Cuffie (Institut Seni Indonesia Yogyakarta, 2021)
Public art is an art form that is displayed in public spaces; it’s for everyone to enjoy. Its existence creates interests, entertainment, and beautifies the environment. Public art fulfills a variety of functions within the public sphere, providing opportunities for, artistic self-expression; community dialogue; education and enjoyment; inspiring participation in appreciation and creation of art; community problem solving; enhancement of the physical infrastructure and environment; and demarcation, celebration and transformation of places. This research aims to explore the impact public art has on the society. The literature review, document analysis and interview were done to help justify the findings of the investigation. The research found that there are multidimensional impacts of public art in urban environment(s). The perceived benefits of art that is displayed in public spaces either in physical, social, or cultural domains suggest that public art is very prominent in creating liveability and sustainability of the city.Seni publik adalah bentuk seni yang ditampilkan di ruang publik; itu untuk dinikmati semua orang. Keberadaannya menciptakan minat, hiburan, dan memperindah lingkungan. Seni publik memenuhi berbagai fungsi dalam ruang publik, memberikan kesempatan untuk ekspresi diri artistik; dialog komunitas; pendidikan dan kesenangan; partisipasi yang menginspirasi dalam apresiasi dan penciptaan seni; pemecahan masalah masyarakat; peningkatan infrastruktur fisik dan lingkungan; dan demarkasi, perayaan dan transformasi tempat. Penelitian ini bertujuan untuk mengeksplorasi dampak seni publik terhadap masyarakat. Tinjauan pustaka, analisis dokumen dan wawancara dilakukan untuk membantu membenarkan temuan penyelidikan. Penelitian ini menemukan bahwa ada dampak multidimensi seni publik di lingkungan perkotaan. Manfaat yang dirasakan dari seni yang ditampilkan di ruang publik baik dalam ranah fisik, sosial, maupun budaya menunjukkan bahwa seni publik sangat menonjol dalam menciptakan liveability dan keberlanjutan kota.